Social Meaning of Mangara Banua Tongkonan Ceremony in Toraja Society - Sam'un Mukramin; Lukman Ismail (Universitas Trunojoyo Madura, 2018)
As the background of this research, there was an existence of a mismatch between idealism and reality. Social change that lead to a negative change of Westernization or a change that lead to cultural destruction, but in reality therewere many cultures that had been preserved. In this case, the researchers studied the local culture that existed until now. For example, Mangrara Banua Tongkonan ceremony, the researchers saw that only the major of young generation in Tanah Toraja people knew specifically the meaning of Mangrara Banua Tongkonan Ceremony. The type of research was descriptive qualitative research that a method in research the status of community, an object, an event. The location of this research was conducted in Ariang Village, Makale Sub-district, Tana Toraja Regency, with data collection technique were observation and interview with respondents .The results obtained about the meaning of social Mangrara Banua Tongkonan ceremony in Tana Torajawas analyzed descriptively qualitative, it can be concluded that the cause of Mangrara Banua Tongkonan ceremony was still preserved until now because of the value, tradition and the active participation of the community. While the meaning in Mangrara BanuaTongkonan ceremony was connotative and denotative meanings.